Unraveling the Effect of Marketing Mix 7P on Consumer Purchasing Decisions: A Study of Gerai Daging Online Store at PT. XYZ - Salsabila, Syifa; Azizah, Siti; Aprylasari, Dede (CV. Komunitas Dunia Peternakan, 2024)
Nowadays the internet presence allows the exchange of information and communication flows that are not limited by time and space. The increasing number of internet users in Indonesia has led to a new trend globally, which is the online shopping trend. PT XYZ (Persero) is one of Indonesia's state-owned enterprises engaged in the livestock sector. PT XYZ has a retail store that sells livestock products, both fresh dan processed. A marketing mix is a tool that can be used by companies to achieve marketing goals in target markets. The objective of this study is to determine the influence of marketing mix 7p (product, price, promotion, people, process, physical evidence, and place) on consumer purchase decisions at the Gerai Daging online store XYZ. This research used 55 respondents with a purposive sampling technique. The research was conducted by distributing questionnaires to respondents. Data were analyzed using SPSS Version 25 software with multiple regression analysis. The results show that marketing mix 7P which consists of 7 attributes, namely product, price, promotion, people, process, physical evidence, and place, didn't show any influence on purchasing decisions at Gerai Daging online store PT. XYZ either simultaneously or partially.